IPAL Komunal dalam Mengolah Limbah Rumah Tangga di Desa Dutohe Barat - Sulastri Pua Age; Rahman Suleman; Indra Haryanto Ali (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
The village of Dutohe Barat is classified as an emergency sanitation area due to household waste produced by human activities (bathing, washing, and cooking). This activity aims to solve the problem by designing and making the communal wastewater treatment that has been standardized. The sample is liquid waste collected from 5 houses in section 4. Initial data on wastewater quality were obtained were BOD, which initially was 265 mg/l, COD was 290 mg/l, and oil and fat were 27 mg/l. The activity method is carried out in 3 stages (observation, socialization, and evaluation). After going through treatment with this communal wastewater treatment, the results of the reduction in waste pollutants were BOD decreased to 98 mg/l, COD decreased to 90 mg/l, and oil and fat decreased to 10 mg/l. In addition, the output from the wastewater treatment processing is used by farmers to irrigate crops.